Using Debate to develop Writing Skills for IELTS Writing Task 2 among STEM Students - Daria Arzhadeeva; Natalia Kudinova (National Research University Higher School of Economics, 2020)
The paper focuses on the issue of developing essay writing skills in the context of IELTS preparation and explores the issue of whether academic debate can enhance STEM students' ability to structure their essays, develop a smooth progression of ideas, and provide supported and extended arguments, which, in turn, may result in higher scores for the IELTS Task Response and Coherence and Cohesion categories. To answer this, a study was undertaken in the academic years 2016/2017 and 2017/2018 among STEM undergraduate students in the National Research University Higher School of Economics, Moscow, Russia. The study involved two groups of students (36 students in each): the group that attended regular IELTS preparation classes and the other that, in addition to regular classes, attended debate classes where among other things Toulmin's argument structure was taught. At the beginning and end of the experiment both groups submitted essays that were analysed according to IELTS rubrics for Task Response and Coherence and Cohesion, and the presence or absence of the elements of Toulmin's argument structure. In addition, the essays were assessed by an independent IELTS teacher. An independent-samples t-test and Levene's test were utilised to determine the significance of the collected data. The findings revealed that, on average, the students of the experimental group scored well in Task Response and Coherence and Cohesion, yet some results were inconsistent, which requires further research.